The role of parental identity in experiencing climate change anxiety and pro-environmental behaviors - Pinho, Mariana (Frontiers in Psychology, 2025)
IntroductionClimate change is one of society's most severe crisis, presenting a health threat to humans with serious impacts on mental health. Climate anxiety has been identified as an important mental health consequence of climate change.MethodsThe current study examined the role of social psychological characteristics on climate change anxiety and pro-environmental behavior, using a nationally representative sample of Portuguese parents who completed extensive questionnaires.ResultsMore central parental identities negatively correlated with and predicted climate change anxiety, revealing that a central parental identity can be a protective factor against mental health issues. Parental identity centrality also predicted greater engagement in pro-environmental behavior. The findings further showed that environmental identity and climate change perceptions were positively related and predicted higher levels climate change anxiety and pro-environmental behavior. Finally, parental identity centrality was linked to greater pro-environmental behavior through climate change anxiety, bringing important contributions to research on the underlying mechanisms that shape pro-environmental behavior.DiscussionThe findings shed light on the complex mechanisms underlying and influencing climate anxiety and pro-environmental behavior, necessary to mitigate the acute consequences of the climate crisis.